Implementation of Diversion in The Juvenile Criminal Justice System: A Study of Effectiveness and Obstacles - Deni Achmad (Universitas Internasional Batam, 2025)
Diversion is an alternative approach in the juvenile criminal justice system that aims to resolve cases outside the formal justice system while still considering the best interests of the child. This study aims to analyze the effectiveness of the implementation of diversion and identify obstacles that arise in its implementation in Indonesia. The research method used is normative juridical with an approach that focuses on literature studies and analysis of laws and regulations, legal doctrines, and relevant court decisions. The results of the study indicate that normatively, provisions regarding diversion have been regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. However, there are various conceptual and implementation obstacles in its implementation, such as the lack of harmony between legal norms and practices in the field, as well as diverse interpretations of the principle of restorative justice. Diversion that is applied consistently and proportionally has been proven to have the potential to prevent children from the negative impacts of the conventional criminal justice system. Therefore, it is necessary to strengthen regulations, harmonize policies, and increase the understanding of law enforcement officers in order to support the success of the implementation of diversion in a sustainable manner.